Handedness and season of birth: a gender-invariant relation. - Martin, M; Jones, G (1999)
In an earlier study, Dellatolas, Curt and Lellouch (1991) concluded that handedness is not related to season of birth. However, post-hoc exploration of their and other sets of data has shown that there is an apparent tendency for left-handedness to be more prevalent in the period March-July than in the period August-February. The present work tested this seasonal hypothesis prospectively among university students. It was found that the proportion of all left-handed participants who were born in the period March-July was indeed significantly greater than the proportion of all right-handed participants who were born in the same period. Furthermore, the pattern of seasonal influence upon handedness did not vary significantly between females and males. The relation between handedness and season of birth may be linked to seasonal variation in other factors such as the incidence of infectious agents.